Studi Alternatif Substrat Kertas untuk Pengujian Viabilitas Benih dengan Metode Uji Diatas Kertas - Linggar Purbojati; Faiza C. Suwarno (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2006)
Viability of small seed is usually tested with top of paper method using paper substrate, but filter and straw papers commonly used for substrate have become more expensive and scarce recently. The aim of this study was to find an alternative paper substrate for seed viability testing using top of paper method. The study consist of 12 experiments using 12 species i.e. pak choy, white mustard, chinese kale, cauliflower, cabbage, sesame, broccoli, green mustard, lettuce, carrot, red spinach and celery. The experiment was arranged in a Randomized Block Design with 10 replications. Sample of 50 seeds were tested on different paper substrate including straw paper, filter paper, stencil paper, CD paper and sterilized filter paper, to identify the best alternative substrate. Result of the study showed that stencil and CD papers as a substrate for seed viability testing performed 100% similarity compared to straw paper. When filter paper was used as standard substrate, there wasn't any paper has 100% similarity, but straw paper showed the highest (97.22%) followed by stencil paper (88.87%). Based on less than 5% coefficient of variation criteria, stencil paper was the best with 61.11% uniformity of seed viability data followed by straw paper (58.33%). In higher tolerance level with less than 10% coefficient of variance criteria, stencil paper was still the highest with 100% uniformity, followed by straw paper (97.22%). Stencil paper as germination substrate performed similar seed viability to the control straw and filter papers also produced high uniformity data. Stencil paper could be used for substrate viability testing of small seed with top of paper method. Key words : Top of paper method, alternative, paper substrate, viability, coefficient of variance